2017
DOI: 10.21873/anticanres.11906
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Significance of Serum Alcohol Dehydrogenase Isoenzymes and Aldehyde Dehydrogenase Activity in Prostate Cancer Patients

Abstract: The results suggest a potential role of ADH III activity as a parameter included in the panel of markers for PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The role of ALDH as a potential marker for CSCs has been discussed in depth by previous reviews of the literature [20, 6669]. ALDH br cells with tumor-initiating ability have been identified in many types of tissues including breast [47, 60, 61, 7074], liver [75], colon [59, 76, 77], lung [78, 79], prostate [65, 80, 81], pancreas [6264, 82], ovary [83], esophagus [84], stomach [85, 86], bone [87], brain [88], skin [89], and bone marrow [9092]. Particularly instructive are comparative data on ALDH br and ALDH dim subsets within a whole tumor cell population showing that ALDH br cells are more clonogenic and tumorigenic than ALDH dim cells are [93].…”
Section: Aldh As a Marker Of Cancer Stem-like Cellsmentioning
confidence: 99%
“…The role of ALDH as a potential marker for CSCs has been discussed in depth by previous reviews of the literature [20, 6669]. ALDH br cells with tumor-initiating ability have been identified in many types of tissues including breast [47, 60, 61, 7074], liver [75], colon [59, 76, 77], lung [78, 79], prostate [65, 80, 81], pancreas [6264, 82], ovary [83], esophagus [84], stomach [85, 86], bone [87], brain [88], skin [89], and bone marrow [9092]. Particularly instructive are comparative data on ALDH br and ALDH dim subsets within a whole tumor cell population showing that ALDH br cells are more clonogenic and tumorigenic than ALDH dim cells are [93].…”
Section: Aldh As a Marker Of Cancer Stem-like Cellsmentioning
confidence: 99%
“…Esophageal cancer, for instance, has a higher prevalence in populations with a common mutation in ADH [17]. It has been found that the total serum ADH activity was significantly higher in patients with PCa and benign prostatic hyperplasia (BPH) compared to healthy subjects; however, the serum ALDH activity was considerably lower [18]. Interestingly, the same study could not detect substantial differences in ADH and ALDH activity between cancer and BPH groups.…”
Section: The Metabolic Role Of Alcohol In Pcamentioning
confidence: 90%
“…The canonical view of ADH's role in cancer focuses on the accumulation of ADH's oxidative product, acetaldehydes and thus the association with ingested alcohol. 12,15,[21][22][23][24] Contrary to the acetaldehyde model, recent studies investigating interactions between alcohol ingestion, ADH polymorphisms, and cancer risk indicate that suppressed ADH function is associated with cancer. [25][26][27][28][29][30][31][32] It is suggested that less ADH activity either by expression or gene variant within the tissue is associated with cytotoxicity and a proinflammatory phenotype consistent with cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] By contrast, there is inconsistent epidemiological evidence supporting a link between alcohol consumption and PCa. [15][16][17][18] Most studies are primarily conducted in Caucasian populations and do not demonstrate a significant association between alcohol ingestion and PCa risk. However, a study stratified by race demonstrated a statistically significant association between alcohol intake and risk for PCa in African American men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation